Emerson for the twenty-first century: global perspectives on an American icon - Tharaud, Barry; Emerson, Ralph Waldo (Univ. of Delaware Press, 2010)
Emerson, Europe, and beyond -- Barry Tharaud, "Emerson, literary globalism, and the circularity of influence" -- Stephen L. Tanner, "The theme of mind in Emerson's English traits" -- T. S. McMillin, "Beauty meets beast: Emerson's English traits" -- -- Wesley T. Mott, "A tale of three cities: Emerson, Louis-Philippe, and transatlantic uses of great men" -- Susan Dunston, "East of Emerson" -- Steven Adisasmito-Smith, "Transcendental brahmin: Emerson's 'hindu' sentiments" -- Jan Stievermann, "'We want men who can open their eyes wider than to a nationality': Ralph Waldo Emerson's vision of an American world literature" -- II. Emerson and science -- Michael P. Branch, "Paths to nature: Emerson's early natural history lectures" -- Branka Arsic, "Nocturnal outings: Emerson on dreams" -- David M. Robinson, "British science, the London lectures, and Emerson's philosophical reorientation" -- Laura Dassow Walls, "'Every truth tends to become a power': Emerson, Faraday, and the minding of matter" -- III. Emerson thinking -- Gayle L. Smith, "Emerson on nature and the rhetoric of thought" -- David Larocca, "Seeing metaphors" -- John Ronan, "Emerson's autobiographical philosophy" -- John Michael, "Death, love, and Emerson's poetry" -- -- George J. Stack and Mary Dimaria, "Emerson and postmodernism" -- IV. Emerson and activism -- David S. Reynolds, "Transcendentalism, transnationalism, and antislavery violence: Concord's embrace of John Brown" -- Len Gougeon, "'Only justice satisfies all': Emerson's militant transcendentalism" -- T. Gregory Garvey, "Simular man: Emerson and cosmopolitan identity" -- Eduardo Cadava, "The guano of history"